Strategi Dakwah YouTube Darussurur Media dalam Meningkatkan Pemahaman Agama - Halwa Sri Wulandari; Malki Ahmad Nasir (Jurnal Riset Komunikasi Penyiaran Islam, 2024)
Abstract. The current da'wah strategy plays an important role in the sustainability of the da'wah activities carried out. The da'wah strategy must be able to develop by collaborating with technology such as the media to help the preferred da'wah activity process. Youtube Darussurur Media was founded as the official digital preaching media of the Central Darussurur Islamic Boarding School which is devoted to providing information and explanations to Muslims regarding Islamic Religious Science and phenomena that occur in society. Therefore, YouTube Darussurur Media works on and publishes its preaching broadcasts with live streaming every day to make it easier for pilgrims who are separated by distance and time to learn about religion anywhere and anytime. This research uses qualitative methods with data collection techniques through interviews, observation and documentation. The author uses SWOT analysis to find out what strengths, weaknesses, opportunities and threats/obstacles exist in order to achieve the goal of da'wah optimally so that it can further increase understanding of religion. The research results obtained regarding the SWOT analysis show that the strengths and opportunities of Youtube Darussurur Media appear to be greater than the weaknesses and threats/obstacles so that it can be said to have a major influence on increasing understanding of religion. Abstrak. Strategi dakwah saat ini memegang peranan penting dalam keberlangsungan kegiatan dakwah yang dilakukan. Strategi dakwah harus dapat berkembang dengan berkolaborasi dengan teknologi seperti media untuk membantu proses kegiatan dakwah yang diinginkan. Youtube Darussurur Media didirikan sebagai media dakwah digital resmi Pondok Pesantren Darussurur Pusat yang dikhususkan untuk memberikan informasi dan penjelasan kepada umat Islam terkait Ilmu Agama Islam dan fenomena yang terjadi di masyarakat. Oleh karena itu, Media YouTube Darussurur menggarap dan mempublikasikan siaran dakwahnya dengan live streaming setiap hari untuk memudahkan jamaah yang terpisah jarak dan waktu untuk belajar agama dimanapun dan kapanpun. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Penulis menggunakan analisis SWOT untuk mengetahui apa saja kekuatan, kelemahan, peluang dan ancaman/hambatan yang ada agar dapat mencapai tujuan dakwah secara optimal sehingga dapat lebih meningkatkan pemahaman agama. Hasil penelitian yang diperoleh mengenai analisis SWOT menunjukkan bahwa kekuatan dan peluang dari Media Youtube Darussurur terlihat lebih besar dibandingkan dengan kelemahan dan ancaman/hambatannya sehingga dapat dikatakan memiliki pengaruh yang besar dalam meningkatkan pemahaman agama.